Quality of Life and Welfare Spaces in Maribor’s Koroška Vrata District: Mapping and Interviews - Koyun, Ezgi; Ozer, Lucien; Tobola, Michal; Bravo-Fabian, Marco; Tosi, Maria Chiara (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
This study examines the role of public or “welfare” spaces in shaping quality of life in the Koroška Vrata neighbourhood of Maribor, Slovenia. Using direct observation and twelve semi-structured interviews, it analyses residents’ perceptions of mobility, safety, and social interaction. Findings indicate that compact urban design, abundant green spaces, and accessible services promote well-being and a strong sense of safety. While minor issues were raised regarding public transport, football-related disturbances, and e-bikes, residents overall considered the neighbourhood highly liveable and expressed little need for change.